Corn Growth and Yield on Suboptimal Upland Soil After Amended with Biochar and Low Levels of Fertilizer in West Kalimantan, Indonesia - Sutarman Gafur; Saeri Sagiman; Tatang Abdurrahman (Journal of Tropical Upland Resources (J. Trop. Upland Res.), 2020)
Biochar is already well-known as a soil amendment material that has great potential to improve degraded soil properties. However, in order to maximize its role in improving important soil characteristics to support plant growth, it needs to be combined with other potential materials. In this study we are seeking a treatment package that is potentially useful and locally affordable. This experiment is designed to study the effects of biochar and low input of NPK treatment packages on corn growth and yield in suboptimal upland soil of West Kalimantan, and to study the impact of these treatments on some important soil characteristics. Four treatment levels were used: T0 (control), T1 (Biochar 5% (W/W), and NPK 300kg/ha), T2 (Biochar 5%, and NPK 600 kg/ha), T3 (Biochar 10% and NPK300 kg/ha, and T4 (Biochar 10% and NPK 600 kg/ha). Each treatment had four replications. The results show that total plant dry weight increased from 151 g/plant (T1) to 237 g/plant (T4), while total corn production increased from 12.9 (T1) to 15.7 ton/ha (T4). Furthermore, all treatment packages also significantly increased soil pH, C-organic content, CEC, and soil C/N ratios. Moreover, the content of N, P, K, in the soil by the end of the experiment also increased on average 163, 1143, and 432%, respectively. In short, all biochar based treatments significantly increased plant growth, yields, and some important soil charactersitics. We highly recommend T3, with lower NPK levels than normally recommended, as a treatment package to be further field tested in suboptimal upland soil in West Kalimantan.